2012
DOI: 10.1111/j.1872-034x.2012.01075.x
|View full text |Cite
|
Sign up to set email alerts
|

Quercetin improves bone strength in experimental biliary cirrhosis

Abstract: These data suggest that quercetin can significantly improve bone strength particularly due to increasing bone formation in biliary cirrhosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 34 publications
1
7
0
Order By: Relevance
“…Our study was also in agreement with finding of Hoda Derakhshanian & et al's in 2012 study where they reported that blood level of osteocalcin in rats was significantly increased after use of Quercetin for study of bone metabolic complications resulted from biliary cirrhosis indicating improving bone strength [35]. As in table 3; use of quercetin led to elevation of serum calcium, this finding is similar to finding of Marwan A.…”
Section: Discussionsupporting
confidence: 92%
“…Our study was also in agreement with finding of Hoda Derakhshanian & et al's in 2012 study where they reported that blood level of osteocalcin in rats was significantly increased after use of Quercetin for study of bone metabolic complications resulted from biliary cirrhosis indicating improving bone strength [35]. As in table 3; use of quercetin led to elevation of serum calcium, this finding is similar to finding of Marwan A.…”
Section: Discussionsupporting
confidence: 92%
“…Osteoporosis and increased fracture risk are common complications in patients with primary biliary cholangitis/cirrhosis. Using a rat model of osteoporosis induced by complete bile-duct ligation, the animals receiving quercetin (150 µmol/kg/day) for four weeks showed reversal of the deteriorating effects of cirrhosis on bone strength and histomorphometric indices of trabecular and cortical bones [42]. The use of high-dose vitamin A (retinoic acid) has been reported to cause reductions in BMD and structural bone parameters [61].…”
Section: Type Of Animalmentioning
confidence: 99%
“…It has been shown that estrogen enhances osteoblast differentiation and bone formation and the conditioned medium of estrogentreated osteoblast cultures inhibits osteoclast development. Many special properties of quercetin make it an ideal candidate substance for the prevention and treatment of diabetic osteopenia (9).…”
Section: Introductionmentioning
confidence: 99%